Artificial food dyes are toxic: Neurobehavioral implications in children - Gokul Sudhakaran (Brain and Spine)
Emerging research highlights the potential neurobehavioral impacts of synthetic food dyes on children, prompting a reevaluation of their safety and regulatory standards. This letter discusses recent findings that associate synthetic food dyes with adverse behavioral outcomes, such as hyperactivity, particularly in children with or without identified behavioral disorders. It calls for updated regulatory guidelines that reflect current research, advocating for protecting children's behavioral health.